1978
DOI: 10.1051/rnd:19780407
|View full text |Cite
|
Sign up to set email alerts
|

Plasma calcitonin and parathyroid hormone levels in growing pigs on different diets. I. — High phosphorus diet

Abstract: Summary. Ten Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Zayed et al, have shown that calcitonin levels increase after ingestion of food (without specifying the type of food) [ 66 ]. A study in pigs showed that a diet high in phosphorus increased calcitonin levels [ 67 ], while a study in rats showed that a diet high in fat increased calcitonin levels [ 68 ].…”
Section: Environmental Factors That Affect Pth and Calcitonin Levelsmentioning
confidence: 99%
“…Zayed et al, have shown that calcitonin levels increase after ingestion of food (without specifying the type of food) [ 66 ]. A study in pigs showed that a diet high in phosphorus increased calcitonin levels [ 67 ], while a study in rats showed that a diet high in fat increased calcitonin levels [ 68 ].…”
Section: Environmental Factors That Affect Pth and Calcitonin Levelsmentioning
confidence: 99%